2005
DOI: 10.1002/bip.20252
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of a hybrid high‐molecular‐weight glutenin subunit from a transgenic hexaploid wheat

Abstract: The high-molecular-weight glutenin subunits (HMW-GS) of wheat gluten in their native form are incorporated into an intermolecularly disulfide-linked, polymeric system that gives rise to the elasticity of wheat flour doughs. These protein subunits range in molecular weight from about 70 K-90 K and are made up of small N-terminal and C-terminal domains and a large central domain that consists of repeating sequences rich in glutamine, proline, and glycine. The cysteines involved in forming intra- and intermolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The height of the islands, 5 nm, is consistent with measurements of the diameter of the ω‐gliadin molecule made by Thomson and coworkers17 using STM and SAXS and therefore suggests that molecules adopt a side‐on conformation to the mica surface (i.e., with the long axis parallel to the surface). It should be noted that 5 nm is greater than the diameter expected for a purely poly‐ L ‐proline II helical structure (∼1 nm); however; it is within the range expected for the diameter of a β‐spiral consisting of poly‐ L ‐proline II and β‐reverse turn (1.2–8 nm) 8. The results for ω‐gliadin adsorption onto mica are consistent with the adsorption of the related protein C hordein onto mica, which also adsorbed in parallel to the surface and with apparent preference to the edges of preadsorbed structures 6…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The height of the islands, 5 nm, is consistent with measurements of the diameter of the ω‐gliadin molecule made by Thomson and coworkers17 using STM and SAXS and therefore suggests that molecules adopt a side‐on conformation to the mica surface (i.e., with the long axis parallel to the surface). It should be noted that 5 nm is greater than the diameter expected for a purely poly‐ L ‐proline II helical structure (∼1 nm); however; it is within the range expected for the diameter of a β‐spiral consisting of poly‐ L ‐proline II and β‐reverse turn (1.2–8 nm) 8. The results for ω‐gliadin adsorption onto mica are consistent with the adsorption of the related protein C hordein onto mica, which also adsorbed in parallel to the surface and with apparent preference to the edges of preadsorbed structures 6…”
Section: Resultsmentioning
confidence: 63%
“…Adsorption to the hydrophobic HOPG surface was much more rapid than when hydrophilic mica was used, indicating that protein–protein interactions were the dominant factor in controlling the adsorption behavior in this system. Recently, McIntire et al8 have used noncontact AFM to study the conformation of the high‐molecular‐weight glutenin subunits of wheat adsorbed to hydrophilic and hydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies showed that proteins form fibrils at the atomic level that possibly align side by side probably due to hydrogen bond formation (Humphris, McMaster, Miles, Gilbert, Shewry & Tatham, 2000;Mackintosh, Meade, Healy, Sutton, Larsen, Squires et al, 2009;McIntire, Lew, Adalsteins, Blechl, Anderson & Kasarda, 2005). However, it is stressed that interactions of proteins with the surface of the mica and sample deposition protocols may contribute to fibril formation.…”
Section: Microstructure Of Gluteninsmentioning
confidence: 91%
“…All images are reproduced by permission. Clockwise: McMaster, Miles, Kasarda, et al, 1999;McMaster, Miles, Wannerberger, et al, 1999;McIntire et al, 2005;Jiang et al, 2008;Kontogiorgos & Goff, 2006, respectively).…”
Section: Micro Scale (µM) Macro Scale (> Mm)mentioning
confidence: 98%
“…Conformations and molecular interactions of wheat storage proteins have been extensively investigated using various techniques such as atomic force microscopy (AFM) (McIntire et al, 2005;McMaster et al, 2000McMaster et al, ,1999Paananen et al, 2006), Raman optical activity (ROA) (Blanch et al, 2003), Fourier transform infrared (FTIR) spectroscopy (Feeney et al, 2003;Georget and Belton, 2006;Li et al, 2006;Pezolet et al, 1992), 1 H magic angle spinning nuclear magnetic resonance (MAS NMR) (Alberti et al, 2001), small angle X-ray scattering (SAXS) (Thomson et al, 1999), circular dichroism (CD) spectroscopy (Kieffer et al, 2007), and intrinsic viscosity measurement (Cole et al, 1984;Ewart, 1980;Field et al, 1987). The interaction between layers of a-gliadin has been studied by the surface force technique (Wannerberger et al, 1997).…”
Section: Introductionmentioning
confidence: 99%